The review of the patterns of presentation and various prognostic factors in male breast cancer patients (Medical Journal of Indonesia, 2001)
This study was aimed to analyze the patterns of presentation, various prognostic factors and therapeutic modalities for the management of breast cancer in male patients. Thirty cases of male breast cancer were treated with radiotherapy at our department between 1983 and 1997. All the patients were treated with radiotherapy besides surgery (26) and chemotherapy (12). Radical mastectomy was performed in 18 patients, while 6 patients were treated with modified radical mastectomy and 2 patients with simple mastectomy. The post operative radiotherapy was applied at the dose of 50 Gy in 25 fractions over a period of five weeks. The chemotherapy was administered in an adjuvant setting. All the patients were received hormonal therapy. Four patients were lost to follow up. The follow up period ranged from 10-92 months with a median of 38 months. The disease-free survival at 2 and 5 years were 87.7% and 54.67%, respectively. One patient recurred locally, whereas 5 patients had distant metastasis. The age, lymph node status at presentation and presence of distant metastasis were the important prognostic factors. At present, the trend is to treat male breast cancer patients like those of females stage per stage. More randomized studies are required for optimizing therapeutic approach. (Med J Indones 2001; 10: 84-7) Keywords: male breast cancer, radiotherapy, chemotherapy, surgery